If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9 = 3(t + 14) Reorder the terms: 9 = 3(14 + t) 9 = (14 * 3 + t * 3) 9 = (42 + 3t) Solving 9 = 42 + 3t Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add '-3t' to each side of the equation. 9 + -3t = 42 + 3t + -3t Combine like terms: 3t + -3t = 0 9 + -3t = 42 + 0 9 + -3t = 42 Add '-9' to each side of the equation. 9 + -9 + -3t = 42 + -9 Combine like terms: 9 + -9 = 0 0 + -3t = 42 + -9 -3t = 42 + -9 Combine like terms: 42 + -9 = 33 -3t = 33 Divide each side by '-3'. t = -11 Simplifying t = -11
| 7x+16=2x | | 13=-4 | | 8=4(y-18) | | -7x-8=8 | | 5b=-10+6b | | 28x+11=1 | | 2y^3=0 | | 7x+5=9z-5 | | 8v=-344 | | k+-15k+7=-7 | | 5b=200 | | 6cos(x)-4=0forx | | 6*cos(x)-4=0 | | x^2+px-9=(x-1)(x+q) | | -5t+12t+9t=-16 | | 8v(8v)= | | 2x^2+10x+30= | | 3f-8=6f+10 | | 28=2(-6+x) | | 5x+mk=7k | | 2(2x+3)-4=2x+5 | | -2(r+7)=14 | | 2x^2+12x+30= | | 4+4s=-8 | | -12/s=4 | | 2+(15)x=-7 | | 7-5x=10-(6x-7) | | 4x(x-12)=20 | | 2+3b=c | | 7r-15=3r+21 | | -6(8f+3)=26-7f | | m3-7=-10 |